2003
DOI: 10.1016/j.cub.2003.11.053
|View full text |Cite
|
Sign up to set email alerts
|

PKD2 Cation Channel Is Required for Directional Sperm Movement and Male Fertility

Abstract: Sperm of both mammals and invertebrates move toward specific sites in the female reproductive tract. However, molecular mechanisms for sperm to follow directional cues are unknown. Here, we report genetic analysis of Drosophila Pkd2 at 33E3 (Pkd2, CG6504), which encodes a Ca(2+)-activated, nonselective cation channel homologous to the human Pkd2 autosomal dominant polycystic kidney disease (ADPKD) gene. The PKD2 family of genes has been implicated in sensory responses through protein localization on primary ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
84
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 16 publications
3
84
1
Order By: Relevance
“…3A). Western blotting showed that neither wild type size nor truncated Met 1 -Gln 729 PKD2 protein is produced by Pkd2 ko67 homozygote (10). This could be explained by possible instability of the truncated Met 1 -Gln 729 peptide or that the truncated peptide is never made due to the additional changes introduced into the Pkd2 ko67 allele during the targeted knock-out procedure.…”
Section: Reverse Transcription-pcr Analysis-formentioning
confidence: 92%
See 4 more Smart Citations
“…3A). Western blotting showed that neither wild type size nor truncated Met 1 -Gln 729 PKD2 protein is produced by Pkd2 ko67 homozygote (10). This could be explained by possible instability of the truncated Met 1 -Gln 729 peptide or that the truncated peptide is never made due to the additional changes introduced into the Pkd2 ko67 allele during the targeted knock-out procedure.…”
Section: Reverse Transcription-pcr Analysis-formentioning
confidence: 92%
“…The allele used in this study is Pkd2 ko67 that was derived from the integration of a mutated Pkd2 donor into the endogenous Pkd2 locus (10). Pkd2 ko67 contains a tandem duplication of Pkd2 with one copy carrying the BamHI and the other copy carrying the MunI frameshift mutations (see Fig.…”
Section: Reverse Transcription-pcr Analysis-formentioning
confidence: 99%
See 3 more Smart Citations